2012
DOI: 10.1074/jbc.m112.366377
|View full text |Cite
|
Sign up to set email alerts
|

Synergic and Opposing Activities of Thermophilic RecQ-like Helicase and Topoisomerase 3 Proteins in Holliday Junction Processing and Replication Fork Stabilization

Abstract: Background: RecQ helicases and topoisomerase 3 enzymes play essential functions in all DNA activities, and their malfunctioning is associated with genomic instability. Results: A RecQ-like helicase and topoisomerase 3 from thermophilic archaea interact physically and functionally. Conclusion:The thermophilic enzymes show synergic and antagonistic activities on different DNA substrates. Significance: The results suggest a novel mechanism of modulation of RecQ-like helicases by topoisomerase 3 enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
3
10
0
Order By: Relevance
“…For the direct homolog Hel112 from S. solfataricus, it was previously shown in vitro that Cy-labeled HJ substrates were mostly unwound to Y-shaped intermediates but, unlike our findings, not to ssDNA (44). When we used Cy3-labeled substrates instead of radioactively labeled DNA, we obtained similar results; in addition, we could not completely boil these substrates to ssDNA (data not shown).…”
Section: Figsupporting
confidence: 72%
See 2 more Smart Citations
“…For the direct homolog Hel112 from S. solfataricus, it was previously shown in vitro that Cy-labeled HJ substrates were mostly unwound to Y-shaped intermediates but, unlike our findings, not to ssDNA (44). When we used Cy3-labeled substrates instead of radioactively labeled DNA, we obtained similar results; in addition, we could not completely boil these substrates to ssDNA (data not shown).…”
Section: Figsupporting
confidence: 72%
“…RecQ helicases are referred to as conserved guardians of genomic integrity (69) and are reported to be involved in multiple pathways for the maintenance of genomic stability, including HR (69-73). As was shown for its previously studied ortholog in S. solfataricus (Sso0112 or Hel112) (44,45), we demonstrated that Saci_1500 shows typical RecQ-like DNA binding and unwinding activities. It catalyzes the processing of HR intermediates, such as Holliday junctions and Y-shaped DNA, and unwinds dsDNA with an overhang in a 3=-to-5=-dependent fashion.…”
Section: Figsupporting
confidence: 49%
See 1 more Smart Citation
“…Combined unwinding/branch migration and annealing activities are shared by eukaryotic and archaeal helicases (37)(38)(39)(40)(41). The discovery that PcalRG holds such activities enabling the HJ resolution by a true ATP-dependent mechanism, at least in vitro, might support previous results suggesting the involvement of RG in recombination and/or repair (7)(8)(9)(10).…”
Section: Discussionsupporting
confidence: 77%
“…Substrates used in DNA binding and unwinding assays were prepared by annealing oligonucleotides in appropriate combinations: M-HJ, A1-A2-A3-A4; IM-HJ, A1-A2-A5-A6; Y-shaped Fork, A1-A2; 40 bp-double strand (ds), A2-A7; Flap, A1-21lead (30); dsFork, A1ϩA2 ϩ 30Lag and 21Lead (39). The single strand (ss) 70 bp Lead and Lag oligonucleotides (39) were used for annealing assays.…”
Section: Methodsmentioning
confidence: 99%